Sex Differences in Performance and Pacing Strategies During Sprint Skiing - Andersson, Erik Petrus; Govus, Andrew; Shannon, Oliver Michael; McGawley, Kerry (Frontiers in Physiology, 2019)
Purpose: This study aimed to compare performance and pacing strategies between elite male and female cross-country skiers during a sprint competition on snow using the skating technique. Methods: Twenty male and 14 female skiers completed an individual time-trial prologue (TT) and three head-to-head races (quarter, semi and final) on the same 1,572-m course, which was divided into flat, uphill and downhill sections. Section-specific speeds, choice of sub-technique (i.e., gear), cycle characteristics, heart rate and post-race blood lactate concentration were monitored. Power output was estimated for the different sections during the TT, while metabolic demand was estimated for two uphill camera sections and the final 50-m flat camera section. Results: Average speed during the four races was 12.5% faster for males than females (P < 0.001), while speeds on the flat, uphill and downhill sections were 11%, 18% and 9% faster for the males than females (all P < 0.001 for terrain, sex, and interaction). Differences in uphill TT speed between the sexes were associated with different sub-technique preferences, with males using a higher gear more frequently than females (P < 0.05). The estimated metabolic demand relative to maximal oxygen uptake (VO2max) was similar for both sexes during the two uphill camera sections ( 129% of VO2max) and for the final 50-m flat section ( 153% of VO2max). Relative power output during the TT was 18% higher for males compared to females (P < 0.001) and was highly variable along the course for both sexes (coefficient of variation [CV] between sections 4–9 was 53%), while the same variation in heart rate was low (CV was 3%). The head-to-head races were 2.4% faster than the TT for both sexes and most race winners (61%) were positioned first already after 30 m of the race. No sex differences were observed during any of the races for heart rate or blood lactate concentration. Conclusions: The average sex difference in sprint skiing performance was 12.5%, with varying differences for terrain-specific speeds. Moreover, females skied relatively slower uphill (at a lower gear) and thereby elicited more variation in their speed profiles compared to the males.